2020
DOI: 10.3389/fped.2020.00588
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the NICU on the Acoustic Isolation of a Neonatal Incubator

Abstract: The neonatal intensive care unit (NICU) is a very noisy place as compared to the intrauterine environment. To protect the neonate's health, international guidelines suggest avoiding noise levels above 45 dB in NICUs, but this recommendation is not normally met. The incubator acoustic isolation and the acoustic features of the NICU play important roles in determining the noise measured inside the incubator. In this study, the influence of two types of rooms, one with sound-absorbent covering and the other with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We have regularly observed exceedances of recommended maximum noise limits in our settings, which reflect the daily life in a NICU. Our results are also consistent with previous reports showing attenuation of numerous noise sources generated in the NICU inside an incubator, reducing continuous sound exposure 5 15 23 27 . Other sound sources such as phone ringing, music boxes on top of the incubator, remote alarms in other rooms, conversations, using disinfectant dispensers, or opening windows did not produce any relevant variation in sound pressure level at the incubator microphone 2 .…”
Section: Discussionsupporting
confidence: 93%
“…We have regularly observed exceedances of recommended maximum noise limits in our settings, which reflect the daily life in a NICU. Our results are also consistent with previous reports showing attenuation of numerous noise sources generated in the NICU inside an incubator, reducing continuous sound exposure 5 15 23 27 . Other sound sources such as phone ringing, music boxes on top of the incubator, remote alarms in other rooms, conversations, using disinfectant dispensers, or opening windows did not produce any relevant variation in sound pressure level at the incubator microphone 2 .…”
Section: Discussionsupporting
confidence: 93%
“…Finally, a concern about incubators may be the constant noise of the fan-operated airflow. Even though the American Academy of Pediatrics recommends avoiding sound levels above 45 dB in neonatal care units, some studies demonstrated noise within incubators exceeded these recommendations frequently ( 59 , 60 ), disrupting sleep cycles ( 61 ) and possibly influencing hearing development.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, maintenance and cleaning require technical competence and considerable human resources for dissembling and assembling between patients. Improper maintenance and cleaning increase the risk of malfunction and infection (57,58). Furthermore, the common practice in low-resource settings of placing multiple neonates in a single incubator increases the risk of cross-infections (55).…”
Section: Incubatorsmentioning
confidence: 99%
“…Therefore, in this experiment, the influence of the resonant frequencies of the room can be considered negligible. However, the resonant frequencies of rooms with acoustic reflective surfaces -like NICUs- may influence the T of the incubator, especially considering that the acoustic insulation of the incubator is very poor ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%